Superhydrophobic microspiked surface structures by ultrashort laser patterning. (3rd October 2021) - Jagdheesh, R.; Kopeček, J.; Brajer, J.; Mocek, T.
ABSTRACT: In this study, self-organised microspiked surface structures were fabricated with a picosecond laser source on austenite stainless steel. The laser-processed surface structures were subjected to low-temperature annealing for chemical modification to reduce the surface free energy of the metal oxides formed due to laser processing. The low-temperature treatment accelerates the adsorption of organic contamination, leading to the formation of ultralow water adhesion surface in few hours compared to the prolonged ageing process. The effect of the number of pulses/spot (PPS) and fluence with respect to the geometrical shape and its impact on wetting behaviour has been systematically investigated. The density of the nanoscale protrusions and the overlay of spongy porous nanoscale structures were influenced by the number of PPS and applied energy density. The multi-scale structures generated with a fluence of 1.3 J/cm 2 showed superhydrophobic character with a high contact angle about 158 ± 3° and low contact angle hysteresis <5°.